The Psychological and Behavioural Determinants of Mutual Fund Investment Decisions in Bengaluru: A Mixed-Method Approach - Uma, B.; Maheswari , Dr.V. (International Journal of Accounting and Economics Studies, 2025)
Purpose: This study examines the psychological and behavioural reasons that guide individuals in Bengaluru when they invest in mutual funds, emphasising how cognitive biases, socio-economic circumstances, and insights from behavioural finance come together to shape every choice. By doing so, the research seeks a clearer picture of how mutual-fund investors make decisions amid a fast-changing financial landscape.Study Design/Methodology/Approach: A mixed-method framework was adopted, pairing in-depth ideas collected from focus-group interviews with quantitative results gathered using a structured questionnaire. Analysts then applied regression and chi-square tests, backed by NVIVO software, to sort out how these psychological and socio-economic factors jointly steer real investment behaviour.Findings: Results show that psychological forces- above all, overconfidence, herd behaviour, and common cognitive traps-still drive mutual fund choices in Bengaluru. The familiar ideas of heuristics and prospect theory reveal the bias behind such moves, as investors often follow easy rules or recoil more strongly from losses than they chase gains. Alongside these forces, age, income, education, and basic financial literacy remain vital in shaping each investor’s taste for risk.Originality/Value: By focusing on Bengaluru investors, this research uncovers distinct psychological and behavioural patterns that steer mutual fund choices in that city. It highlights how socio-economic background shapes these decisions, thus adding fresh evidence to the expanding behavioural finance discussion in emerging markets.Research Implications: The results point to the need for financial education and personalised advisory services that can soften the impact of common cognitive biases. The study also urges fund managers and advisors to weave behavioural insights into their strategies so investors make clearer, better judgments in rapidly growing markets such as Bengaluru.